On the significance of estimating cardiorespiratory coupling strength in sports medicine - Abreu, Raphael Martins de; Cairo, Beatrice; Porta, Alberto (Frontiers in Network Physiology, 2023)
The estimation of cardiorespiratory coupling (CRC) is attracting interest in sports physiology as an important tool to characterize cardiac neural regulation genuinely driven by respiration. When applied in sports medicine, CRC measurements can provide information on the effects of training, pre-competition stress, as well as cardiovascular adjustments during stressful stimuli. Furthermore, since the CRC is strongly affected by physical activity, the study of the CRC can guide the application of specific training methods to optimize the coupling between autonomic activity and heart with possible effects on performance. However, a consensus about the physiological mechanisms, as well as methodological gold standard methods to quantify the CRC, has not been reached yet, thus limiting its application in experimental settings. This review supports the relevance of assessing CRC in the sports medicine, examines the possible physiological mechanisms involved, and lists a series of methodological approaches. CRC strength seems to be increased in athletes when compared to sedentary subjects, in addition to being associated with positive physiological outcomes, such as a possible better interaction of neural subsystems to cope with stressful stimuli. Moreover, CRC seems to be influenced by specific training modalities, such as inspiratory muscle training. However, the impact of CRC on sports performance still needs to be better explored through ad-hoc physical exercise tests and protocols. In addition, this review stresses that several bivariate and multivariate methods have been proposed to assess CRC, thus opening new possibilities in estimating cardiorespiratory interactions in athletes.